FRUGAL INNOVATION AND ITS EFFECT PIONEER ADVANTAGE FIELD STUDY IN TOTERS EXPRESS DELIVERY COMPANY - Yasameen yaseen hussein (Scholar Express Journals, 2025)
This study explores the concept of frugal innovation and its impact on achieving pioneer Advantage in the context of the express delivery sector. Focusing on the express delivery company, Totters, the study examines how frugal innovations in terms of cost and resource efficiency can provide a competitive advantage in a highly dynamic market. Data were collected through a survey of (85) employees of the company under study and analyzed using the advanced statistical program Smart PLS V.4 to assess the role of streamlined operations, affordable solutions, and customer-centric strategies. The results reveal that frugal innovation significantly enhances a company’s ability to lead the market by delivering high value with limited resources. Furthermore, the study highlights the critical interaction between innovation and strategic positioning in supporting long-term competitiveness. This research provides practical insights for companies aiming to leverage frugal innovation as a path to achieving pioneer Advantage, especially in resourceconstrained environments.
Keywords: Frugal Innovation; Pioneer Advantage; Totters Express Delivery Company